AN EXPEDIENT ENTRY TO CEPHALOSPORIN DERIVATIVES WITH CYCLIC SUBSTITUENTS AT THE 3-POSITION BY [3+2] CYCLOADDITION REACTIONS - KANG, HY; CHO, YS; KOH, HY; CHANG, MH (GEORG THIEME VERLAG, 1995)
Synthesis of cephalosporin derivatives with cyclic substituents at the 3-position was efficiently achieved by the intramolecular 1,3-dipolar cycloaddition reactions. It has been confirmed that 3-alkylidenecepham-4-carboxylic acids derivatives could be utilized as efficient intermediates for preparation of the desired cephalosporin derivatives. Efficiency of the synthetic route was shown using a nitrone and a nitrile oxide derivatives as dipole components.
Keywords: ORGANIC-SYNTHESIS; SAMARIUM(II) IODIDE; LANTHANIDES; REDUCTION; HALIDES